Eye movement desensitisation and reprocessing as a potential treatment for substance use disorders: study protocol - Daniel Folch Sanchez; Chrysanthi Blithikioti; Flavia Piazza; Laura Nuño; Laura Blanco; Arturo Rodríguez-Rey; Emma Muñoz-Moreno; Mercè Balcells-Oliveró; Laia Miquel (European Journal of Psychotraumatology)
Background: Prior exposure to traumatic events significantly increases the risk of developing substance use disorders (SUD), while having SUD, in turn, elevates the likelihood of encountering additional traumatic events. Despite this relationship, the consequences of trauma frequently go undetected and untreated in this population. The trauma-focused intervention eye movement desensitisation and reprocessing (EMDR), a first-line treatment for post-traumatic stress disorder (PTSD), has shown promising therapeutic potential in SUD patients. However, its underlying neurobiological mechanisms remain unclear. This study aims to investigate the efficacy of EMDR in SUD patients with comorbid psychological trauma. Additionally, potential mechanisms of action of the intervention will be explored. The primary hypothesis is that integrating EMDR into standard SUD treatment will enhance substance use prognosis.Methods: Sixty-four patients with SUD and trauma symptomatology will be randomised into two groups. One group will receive EMDR trauma-focused intervention in 6-8 sessions alongside treatment as usual (TAU) (n = 32), while the control group will receive TAU only (n = 32). The primary outcome will be the time to relapse, assessed at baseline, immediately after treatment, and at 1- and 3-months follow-up. Additional measures include post-traumatic, anxiety, depressive symptoms and biological markers (hair/salivary cortisol levels, eye blink conditioning, and resting-state fMRI). Survival analysis and linear mixed models will be used to assess treatment effects. The trial is registered on ClinicalTrials.gov (NCT05488691).Discussion: This study addresses a critical gap in scientific literature and clinical practice by evaluating the efficacy of EMDR, in patients with SUD and comorbid trauma symptoms, through a combination of clinical and biological markers. The findings could lead to integration of personalised, trauma-focused interventions into public health services for patients with SUD.